The International Peacemaking Dilemma: Ousting or Including the Villains?. Issue 4 (21st September 2020) - Nathan, Laurie
Abstract: International actors engaged in peacemaking in armed conflicts are often confronted by a moral dilemma: whether to seek to oust the villains by coercive means, or to promote mediation that includes the villains and may lead to a power‐sharing deal with them. This article analyzes the peacemaking dilemma through a constructivist perspective on international norms. It contributes to the constructivist literature, which concentrates on contestation between "good" and "bad" norms, by developing a theoretical framework for understanding moral dilemmas as a "situational incompatibility of good norms". The peacemaking dilemma entails a situational incompatibility between the norm of promoting and maintaining peace and security on the one hand, and the norms of promoting justice, accountability and democratization on the other. The dilemma is difficult to resolve because all these norms are constitutive of the UN and because of strategic uncertainty in armed conflicts. The theoretical framework is applied to the conflicts in Côte d'Ivoire, Libya and Syria.